Dextrose solution for priming and rinsing the extracorporeal circuit in hemodialysis patients: A prospective pilot study. Issue 11 (November 2021) - Rootjes, Paul A; Penne, Erik Lars; Ouellet, Georges; Dou, Yanna; Thijssen, Stephan; Kotanko, Peter; Raimann, Jochen G
Introduction: Excess sodium intake and consequent volume overload are major clinical problems in hemodialysis (HD) contributing to adverse outcomes. Saline used for priming and rinsing of the extracorporeal circuit is a potentially underappreciated source of intradialytic sodium gain. We aimed to examine the feasibility and clinical effects of replacing saline as the priming and rinsing fluid by a 5% dextrose solution. Materials and methods: We enrolled non-diabetic and anuric stable HD patients. First, the extracorporeal circuit was primed and rinsed with approximately 200–250 mL of isotonic saline during 4 weeks (Phase 1), subsequently a similar volume of a 5% dextrose solution replaced the saline for another 4 weeks (Phase 2), followed by another 4 weeks of saline (Phase 3). We collected data on interdialytic weight gain (IDWG), pre- and post-dialysis blood pressure, intradialytic symptoms, and thirst. Results: Seventeen chronic HD patients (11 males, age 54.1 ± 18.7 years) completed the study. The average priming and rinsing volumes were 236.7 ± 77.5 and 245.0 ± 91.8 mL respectively. The mean IDWG did not significantly change (2.52 ± 0.88 kg in Phase 1; 2.28 ± 0.70 kg in Phase 2; and 2.51 ± 1.2 kg in Phase 3). No differences in blood pressures, intradialytic symptoms or thirst were observed. Conclusions: Replacing saline by 5% dextrose for priming and rinsing is feasible in stable HD patients and may reduce intradialytic sodium loading. A non-significant trend toward a lower IDWG was observed when 5% dextrose was used. Prospective studies with a larger sample size and longer follow-up are needed to gain further insight into the possible effects of using alternate priming and rinsing solutions lowering intradialytic sodium loading. Trial registration: Identifier NCT01168947 (ClinicalTrials.gov).